2020
DOI: 10.1101/2020.09.26.314179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal patterns inIxodes ricinusmicrobial communities: an insight into tick-borne microbe interactions

Abstract: BackgroundTicks transmit pathogens of medical and veterinary importance, and represent an increasing threat for human and animal health. Important steps in assessing disease risk and developing possible new future control strategies involve identifying tick-borne microbes, their temporal dynamics and interactions.MethodsUsing high throughput sequencing, we studied the microbiota dynamics of Ixodes ricinus from 371 nymphs collected monthly over three consecutive years in a peri-urban forest. After adjusting a P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 108 publications
1
30
4
Order By: Relevance
“…111,112 It is important to note here that several studies have demonstrated that microbial communities in female ticks were frequently less diverse than in males and that microbial composition varied according to tick sex. 50,76,105,106 Finally, and as has already been emphasized by Pollet et al, 75 while endosymbionts are mainly known to be vertically transmitted to progeny and thus be strongly detected in tick ovaries, 70,113 multiple studies suggest their presence in other tick organs such as Malpighian tubules, salivary glands or the midgut. 6,84,86,[114][115][116] Clear variations in tick microbial communities can be observed according to the anatomical region within the tick when comparing these studies.…”
Section: Ti Ck MI Crob Ial Communit Y Dynamic Smentioning
confidence: 77%
See 4 more Smart Citations
“…111,112 It is important to note here that several studies have demonstrated that microbial communities in female ticks were frequently less diverse than in males and that microbial composition varied according to tick sex. 50,76,105,106 Finally, and as has already been emphasized by Pollet et al, 75 while endosymbionts are mainly known to be vertically transmitted to progeny and thus be strongly detected in tick ovaries, 70,113 multiple studies suggest their presence in other tick organs such as Malpighian tubules, salivary glands or the midgut. 6,84,86,[114][115][116] Clear variations in tick microbial communities can be observed according to the anatomical region within the tick when comparing these studies.…”
Section: Ti Ck MI Crob Ial Communit Y Dynamic Smentioning
confidence: 77%
“…densities. 86 Similarly, Lejal et al 50 documented the existence and annual recurrence of marked temporal shifts in tick microbial community dynamics in I ricinus. Excluding results from Clow et al, 72 prior works also demonstrated the strong influence of biogeography on tick microbiome structure and composition from different tick species, both at state or regional scales 71,76,91,100-102 and at more local scales, between ticks collected from either the forest or the ecotone.…”
Section: Ti Ck MI Crob Ial Communit Y Dynamic Smentioning
confidence: 98%
See 3 more Smart Citations